2012
DOI: 10.1113/expphysiol.2012.066712
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity of the renin–angiotensin and sympathetic nervous systems is required for regulation of the blood pressure in rats fed a low‐protein diet

Abstract: New Findings r What is the central question of this study?Is the increase in blood pressure observed in rats fed a low protein diet due to overactivation of sympathetic and renin angiontensin systems? r What is the main finding and its importance?The data show an increase in the expression of angiotensin II type 1 receptors and an incrased sympathetic activity in this experimental model, suggesting that both systems are contributing to the high blood pressure observed in these animals.Previous studies have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 28 publications
5
29
0
Order By: Relevance
“…These results indicate an increased α1-adrenergic receptor activity in these animals, with only 14 days of food restriction, which would be necessary to sustain the blood pressure. Importantly, animals fed a low protein diet, for 35 days, present a higher vasomotor tone that could be due to an increased sympathetic efferent activity [16,40], corroborating the idea that dietary restrictions can lead to increased SNS activation to the arteries. The pronounced tachycardic response in these animals could be, possibly, the result of the pronounced hypotension, which would activate the baroreflex circuit leading to a marked activation of the SNS to the heart.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These results indicate an increased α1-adrenergic receptor activity in these animals, with only 14 days of food restriction, which would be necessary to sustain the blood pressure. Importantly, animals fed a low protein diet, for 35 days, present a higher vasomotor tone that could be due to an increased sympathetic efferent activity [16,40], corroborating the idea that dietary restrictions can lead to increased SNS activation to the arteries. The pronounced tachycardic response in these animals could be, possibly, the result of the pronounced hypotension, which would activate the baroreflex circuit leading to a marked activation of the SNS to the heart.…”
Section: Discussionmentioning
confidence: 71%
“…The analogical signal from the amplifier was digitized by a 12 bit analogical-to-digital converter (PowerLab/400, ADI Instruments, Australia), and the pulsatile arterial pressure recorded at 1000 Hz by the software Chart 7.0 for Windows (ADInstruments, Australia). MAP and HR were derived on-line from the pulsatile arterial pressure using pulse-to-pulse analysis [16].…”
Section: Cardiovascular Measurementsmentioning
confidence: 99%
“…Recent experimental and clinical evidence indicates that dysfunction of carotid body chemoreceptors plays a critical role in the progression of cardiorespiratory morbidities associated with baseline sympathetic overactivity, including sleep disorders, congestive heart failure, chronic pulmonary obstructive disease, and hypertension (9,12,13,27,(46)(47)(48). In agreement with this notion, we hypothesize that the enhanced baseline sympathetic and inspiratory motor activities of juvenile offspring from dams subjected to protein restriction during pregnancy and lactation, before the development of hypertension, are dependent, at least in part, on the sensitization of the peripheral chemoreflex.…”
Section: Discussionmentioning
confidence: 99%
“…The offspring of rat dams subjected to a maternal low-protein (LP) 10 diet is a model that is often used to study the mechanisms of maternal undernutrition-related hypertension (6)(7)(8), which has been suggested to be associated with changes in the functioning of the sympathetic nervous system (9,10). However, there is no direct evidence demonstrating that sympathetic vasoconstrictor tonus is elevated in rats subjected to a perinatal LP diet.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies involving protein restriction have shown that many changes in autonomic and hormonal mechanisms controlling the cardiovascular system take place to keep blood pressure close to normal levels (Fyhrquist & Saijonmaa, ; Gomide et al . ; Rodrigues‐Barbosa et al . ).…”
Section: Discussionmentioning
confidence: 99%